Monitoring of insect pollinators of mango (Mangifera indica L.) inflorescence based on citizen science - Ipin Aripin; Topik Hidayat; Nuryani Y Rustaman; Riandi Riandi (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Mango cross-pollination can be encouraged through the presence of pollinating insects, which can be investigated and observed through citizen science activities. This study aims to monitor the presence of insect pollinators of mango (Mangifera indica L.) inflorescence through citizen science activities. The data generated in the study can be used as a reference to determine population trends and the biodiversity of mango insect pollinators. A citizen science approach in participatory research was used to collect and identify the data. A total of 68 volunteer participants from two universities in west Java were involved in this study. The participants had to meet the requirements to have contracted ecology courses. Smartphones and insect identification guidelines and databases at https://www.discoverlife.org/ and https://www.inaturalist.org/ were used as a tool in this research. The identified data were submitted via google form (www.bit.ly/csmangga) and the Inaturalist application for publication. It was discovered that mango inflorescence insect pollinators comprised five orders, 26 families, and 39 species. Diptera and Hymenoptera orders are insects that have the biggest role in mango pollination, and Chrysomya sp. is an insect species found in almost all mango cultivars.